Jatropha chazaroi (Euphorbiaceae), an endangered new species from Apazapan, Veracruz, Mexico - Sánchez-Sánchez, Odilón; Jiménez-Ramírez, Jaime; Arzaba-Villalva, Carlos; Francisco-Gutiérrez, Antonio; Rosales-Lara, Luis Ángel (Phytotaxa, 2023)
Jatropha chazaroi is described and illustrated as a new species from the state of Veracruz, Mexico. It is morphologically similar to J. podagrica but is distinguished by being a tree or shrub devoid of a caudex (vs. shrub with caudex) and lacking persistent and spinescent stipules (vs. having persistent and spinescent stipules). Its flowers possess connate staminate and pistillate calyces and corollas (vs. not connate). Jatropha chazaroi is only known from the municipality of Apazapan, Veracruz, and thrives in shady sites throughout intermittent waterways.